Perbandingan Pengaturan Lembaga Penyelesaian Sengketa Hasil Pemilu Indonesia dengan Uruguay - Wulan, Dewi Sri; Luluardi, Yunas Derta (Sharia Faculty, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Electoral dispute resolution is a crucial aspect in maintaining democratic integrity. This comparative study analyzes fundamental differences between electoral dispute resolution systems in Indonesia through the Constitutional Court and Uruguay through La Corte Electoral, focusing on institutional design and operational effectiveness.The research employs doctrinal legal methodology with comparative and historical approaches, supported by comprehensive literature review from primary and secondary sources. Uruguay's La Corte Electoral, operational since 1924, demonstrates a unique model by integrating regulatory and adjudicative functions within a single autonomous institution. This system differs from Indonesia's, which separates these functions between the Election Commission (KPU), Election Supervisory Body (Bawaslu), and Constitutional Court. In-depth analysis reveals that Uruguay's model offers several significant advantages: first, institutional continuity enabling accumulation of experience and expertise; second, integration of functions resulting in more effective coordination; and third, structural independence strengthening decision legitimacy. These factors contribute to Uruguay's long-term democratic stability. Based on these findings, the research recommends institutional reform in Indonesia through the establishment of a permanent specialized electoral court. This transformation must consider Indonesia's socio-political characteristics, including geographical complexity, demographic diversity, and local political dynamics. Implementation should be conducted gradually, addressing regulatory aspects, institutional capacity, and accountability mechanisms.Practical implications include the need for constitutional amendments, human resource capacity development, and strengthening of legal infrastructure. The theoretical contribution of this research enriches discourse on electoral judicial institutional design in the context of developing democracies. Keywords: Democracy; La Corte Electoral; Constitutional Court; Dispute Resolution